Fear of Flying among Mutah University Students Bassed on some Variables - Basim Aldahadha; Abrar Aladaileh (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
The study aims to identify the level of fear of flying among Mutah University students in light of the variables of gender, nationality, educational level, college, and the number of times of travel. The study sample consisted of 709 students from all faculties of the university. A questionnaire was developed to measure fear of flying. The results indicated that the general average of the level of fear of flying on planes on the variable of fear days before traveling, and the variable of feeling fear upon arrival at the airport came to a low degree, and on the variable of fear of flying when boarding planes came in a medium degree. The results indicated that there were statistically significant differences due to the variables of gender and the number of times of travel. The results were in favor of both females on the number of plane rides and in favor of males for the other dimensions and the overall degree of the scale. The results were in favor of those who traveled more than once on all dimensions of the scale and overall score.